Clinical and Computerized Volumetric Analysis of Posterior Fossa Decompression for Space-Occupying Cerebellar Infarction - Goulin Lippi Fernandes, Eric; Ridwan, Sami; Greeve, Isabell; Schäbitz, Wolf-Rüdiger; Grote, Alexander; Simon, Matthias (Frontiers in Neurology, 2022)
Background and Purpose Surgical decompression of the posterior fossa is often performed in cases with a space-occupying cerebellar infarction to prevent coma and death. In this study, we analyzed our institutional experience with this condition. We specifically attempted to address timing issues and investigated the role of cerebellar necrosectomy using imaging data and conducting volumetric analyses. Methods We retrospectively studied pertinent clinical and imaging data, including computerized volumetric analyses (preoperative/postoperative infarction volume, necrosectomy volume, and posterior fossa volume), from all 49 patients who underwent posterior fossa decompression surgery for cerebellar infarction in our department from January 2012 to January 2021. Results Thirty-five (71%) patients had a Glasgow Coma Scale (GCS) of 14–15 at admission vs. only 14 (29%) before vs. 41 (84%) following surgery. Seven (14%) patients had preventive surgery (initial GCS 14–15, preoperative GCS change ≤ 1). Only 18 (37%) patients had an mRS score of 0–3 at discharge. Estimated overall survival was 70.5% at 1 year. Interestingly, 18/20 (90%) surviving cases had a modified Rankin Scale (mRS) outcome of 0–3 (mRS 0–2: 12/20 [60%]) 1 year after surgery. Surgical timing, including preventive surgery and mass effect of the infarct, in the posterior fossa assessed semi-quantitatively (Kirollos grade) and with volumetric parameters that were not predictive of the patients' (functional) outcomes. Conclusion Posterior fossa decompression for cerebellar infarction is a life-saving procedure, but rapid recovery of the GCS after surgery does not necessarily translate into good functional outcome. Many patients died during follow-up, but long-term mRS outcomes of 4–5 are rare. Surgery should probably aim primarily at pressure relief, and our clinical as well as volumetric data suggest that the impact of removing an infarcted tissue may be limited. It is presumably relatively safe to initially withhold surgery in cases with a GCS of 14–15.